Cytotoxicity and genotoxicity of calcium silicate-based cements on an osteoblast lineage - Ana Lívia GOMES-CORNÉLIO; Elisandra Márcia RODRIGUES; Leticia Boldrin MESTIERI; Thaís de Oliveira Rodrigues Sanzovo FALCOSKI; Christiane Pienna SOARES; Juliane Maria GUERREIRO-TANOMARU; Carlos ROSSA JUNIOR; Mário TANOMARU FILHO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract Several calcium silicate-based biomaterials have been developed in recent years, in addition to Mineral Trioxide Aggregate (MTA). The aim of this study was to evaluate the cytotoxicity, genotoxicity and apoptosis/necrosis in human osteoblast cells (SAOS-2) of pure calcium silicate-based cements (CSC) and modified formulations: modified calcium silicate-based cements (CSCM) and three resin-based calcium silicate cements (CSCR1) (CSCR 2) (CSCR3). The following tests were performed after 24 hours of cement extract exposure: methyl-thiazolyl tetrazolium (MTT), apoptosis/necrosis assay and comet assay. The negative control (CT-) was performed with untreated cells, and the positive control (CT+) used hydrogen peroxide. The data for MTT and apoptosis were submitted to analysis of variance and Bonferroni's posttest (p < 0.05), and the data for the comet assay analysis, to the Kruskal-Wallis and Dunn tests (p < 0.05). The MTT test showed no significant difference among the materials in 2 mg/mL and 10 mg/mL concentrations. CSCR3 showed lower cell viability at 10 mg/mL. Only CSC showed lower cell viability at 50 mg/mL. CSCR1, CSCR2 and CSCR3 showed a higher percentage of initial apoptosis than the control in the apoptosis test, after 24 hours exposure. The same cements showed no genotoxicity in the concentration of 2 mg/mL, with the comet assay. CSC and CSCR2 were also not genotoxic at 10 mg/mL. All experimental materials showed viability with MTT. CSC and CSCR2 presented a better response to apoptosis and genotoxicity evaluation in the 10 mg/mL concentration, and demonstrated a considerable potential for use as reparative materials.